Students' Perception of Teacher Guidance on Reading Learning Based on Results of PISA 2018 - Safari, NFN (Pusat Asesmen dan Pembelajaran, 2020)
The main purpose of this study is to answer the following question; is there any difference between international students' perceptions of teacher guide on learning to read to meet real-life challenges whose country position is above and below the 2018 average Program for International Student Assessment (PISA) score? The data in this study taken from PISA 2018 data that has been released to the public and has been permitted for research and development purposes. The population of this study was 15-year-old students (SMP) throughout the world who were studying in 2018, while the sample was 15-year-old students. PISA test participants was spread in 80 countries. The sample was students who participated in the 2018 PISA test. The data in this study were taken from the students’ test scores and questionnaires that were answered by 612.004 students from 80 countries. Based on the results of the analysis of variants of one path obtained the following results; there is a statistically significant difference (p<0,000) between students’ perceptions of countries below and above the PISA average on the following issues; (1) teacher feedback, (2) improvement of material, and (3) performance improvement in reading, learning to meet real life challenges where the country's position is above and below the average score average PISA 2018, (Sig. 0,000). The conclusion indicates that teachers in countries above the PISA average often provide feedback and provide improved reading material to their students compared to teachers in countries below the PISA average. Teachers in countries below the PISA average provide feedback for performance improvement more often than to teachers in countries above the PISA average. Because the learning dependence of students in countries above the PISA average is higher than students in countries below the PISA average, the frequency of feedback is considered unnecessary.